Teknik Pelaksanaan Evaluasi Program Dalam Pendidikan Islam - Muhammad Miftahul Falah; Muhammad Yahya Ashari (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2024)
For an educational institution to achieve its goals, it must be able to measure, assess, and evaluate all implemented programs. The results of this evaluation will demonstrate the success or failure of a program and determine the appropriate steps to address any issues. It is crucial to choose the appropriate technique for evaluation, as selecting an incorrect method may lead to inaccurate predictions, thus creating further problems for the institution. This article aims to identify the techniques and steps needed for implementing program evaluation in Islamic education. The research conducted is qualitative, using a literature study approach through scientific articles. Based on the literature studied, the evaluation techniques are determined by the aspects that need to be measured. Meanwhile, the final step in the evaluation process is to process and interpret the results, which will help in developing more focused educational programs.